Ion-driven nanograin formation in early-stage degradation of tri-cation perovskite films. Issue 7 (7th February 2022) - Richheimer, Filipe; Toth, David; Hailegnaw, Bekele; Baker, Mark A.; Dorey, Robert A.; Kienberger, Ferry; Castro, Fernando A.; Kaltenbrunner, Martin; Scharber, Markus C.; Gramse, Georg; Wood, Sebastian
Abstract : Nanoscale investigation of operational stability in perovskite films. Scanning probe microscopy is employed to reveal signs of early-stage degradation caused by the formation of local charge imbalance across the film microstructure. Abstract : The operational stability of organic–inorganic halide perovskite based solar cells is a challenge for widespread commercial adoption. The mobility of ionic species is a key contributor to perovskite instability since ion migration can lead to unfavourable changes in the crystal lattice and ultimately destabilisation of the perovskite phase. Here we study the nanoscale early-stage degradation of mixed-halide mixed-cation perovskite films under operation-like conditions using electrical scanning probe microscopy to investigate the formation of surface nanograin defects. We identify the nanograins as lead iodide and study their formation in ambient and inert environments with various optical, thermal, and electrical stress conditions in order to elucidate the different underlying degradation mechanisms. We find that the intrinsic instability is related to the polycrystalline morphology, where electrical bias stress leads to the build-up of charge at grain boundaries and lateral space charge gradients that destabilise the local perovskite lattice facilitating escape of the organic cation. This mechanism is accelerated by enhanced ionic mobility under optical excitation. Our findings highlight the importance of inhibiting the formation of local charge imbalance, either through compositions preventing ionic redistribution or local grain boundary passivation, in order to extend operational stability in perovskite photovoltaics.